Passivating Contact with Phosphorus‐Doped Polycrystalline Silicon‐Nitride with an Excellent Implied Open‐Circuit Voltage of 745 mV and Its Application in 23.88% Efficiency TOPCon Solar Cells. Issue 11 (20th September 2021) - Yang, Qing; Liu, Zunke; Lin, Yiran; Liu, Wei; Liao, Mingdun; Feng, Mengmeng; Zhi, Yuyan; Zheng, Jingming; Lu, Linna; Ma, Dian; Han, Qingling; Cheng, Hao; et al.
Abstract : A P‐doped polycrystalline silicon‐nitride (n‐poly‐SiN x ) as the electron selective collection layer in a tunnel oxide passivated contact (TOPCon) solar cell is reported. The nitrogen content is controlled by the active gas ratio of R  = NH3 /(SiH4  + NH3 ) during the plasma‐enhanced chemical vapor deposition (PECVD) process. The effects of R ratio on the material's composition, crystallinity, surface passivation, and contact resistivity are investigated. The poly‐SiN x contact exhibits improved surface passivation in comparison with the reference poly‐Si without N incorporation. The best double‐sided passivated n‐type alkaline‐polished crystalline silicon wafer with the n‐poly‐SiN x /SiO x manifests the highest implied open‐circuit voltage (i V oc ) of ≈745 mV, with the corresponding single‐sided saturated current density of 1.7 fA cm −2 and the effective lifetime ( τ eff ) of 10 ms at the injection level of ≈1 × 10 15  cm −3 . In contrast, the controlled sample with an n‐poly‐Si/SiO x passivation contact has a maximal i V oc of 738 mV. However, the primary drawback of the N doping is to raise the contact resistivity, but which is still in an acceptable range and shows little effect on the performance of solar cell with full‐area contact. The proof‐of‐concept TOPCon solar cell using the n‐poly‐SiN x /SiO x passivating contact has achieved an efficiency of 23.88%, indicating the potential of the n‐poly‐SiN x for high‐efficiency TOPCon solar cells. Abstract : Phosphorus‐doped poly‐SiN x as a new material, featuring significant nitrogen doping and low crystalline degree, is introduced to passivating contact, leading to excellent passivation quality with a champion i V oc of 745 mV and enabling the efficiency of the proof‐of‐concept tunnel oxide passivated contact solar cell to 23.88%.